Knowledge of elf and Ecuadorian English language teacher attitudes towards English - Rodriguez Estéfano, Julio Alejandro (2022)
This thesis examines the effects of ELF knowledge on the attitudes towards the English language of English teachers in Ecuador. This was mixed research aimed to find the differences between the participants’ attitudes towards learning English before and after an intervention.